Systematic review and classification of: Multisystemic therapy – MST (2. ed.) - Strøm, Henriette Kyrrestad; Handegård, Bjørn Helge (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2017)
Background: The article is a revision of a previous description of the intervention that was published in Ungsinn (Kornør, 2014), and is a systematic review of current knowledge of the effects of Multisystemic Therapy (MST) in a Nordic context. MST is an intensive family- and community-based treatment for adolescents with serious behavioral problems, and is an alternative to incarceration and placement out of home. The review of MST has been revised to conform to new Ungsinn scoring criteria and procedures. Method: The following databases were searched in order to find published articles about the MST intervention: Embase, Medline, Psycinfo, Norart, Cochrane, Cristin, NORA, SCOPUS and SweMed. Six articles, based on three Nordic evaluation studies were included in this review. Results: The results include a summary of the description of MST, the outcome of the effectiveness studies, methodological quality of the research, and implementation quality. MST is well described in several documents including a detailed manual. There are two Norwegian studies and one Swedish study that have examined the effect of MST in a Nordic context. The first Norwegian study and the Swedish study used a randomized controlled design with pre- and posttest measurements collected six months and two years after intake. The second Norwegian study compared a new treatment group (non-randomized sample) with parts of the control group from the first study. The Swedish study additionally reported posttest scores after 5 years based on registry data. Both the Norwegian studies and the Swedish study compared MST with a control group that received regular treatment in child protection services. The Norwegian studies showed positive effects in both short- and long term for the adolescents receiving MST, whereas the Swedish study reported no statistically significant differences between the group receiving MST and those in the control group. All studies were conducted with good methodological quality. The intervention has good procedures to ensure quality implementation. Conclusion: MST is classified at evidence level 4 – Intervention with satisfactory evidence of effectiveness.